In search of John Franklin: the 'Arctic adventures' of Lady Franklin - Brazzelli (Cambridge Scholars Publishing, 2020)
In this chapter, the tragic loss of Sir John Franklin’s expedition in search of the Northwest Passage is investigated from the perspective of Franklin’s wife, who won popular celebrity through her efforts to discover the fate of her beloved husband. Jane Franklin greatly transformed the narrative discourse of Arctic exploration, both through the direct influence she exerted on the search for Franklin and through her rewriting of the language of heroism, suffering and national honour. Her correspondence with British Prime Ministers, Members of Parliament, Lords of the Admiralty offers the private side to a national tragedy. However, Lady Franklin’s letters employ the (female) language of emotion and affection to promote (male) imperial views.